1984
DOI: 10.1016/0022-0531(84)90056-5
|View full text |Cite
|
Sign up to set email alerts
|

Why do some goods bear higher taxes than others?

Abstract: Taxation in an economy containing land and labor is studied. The tax system is a compromise based on the relative power of all groups of individuals. (The model extends one of Aumann and Kurz.) In response to the threat of taxation by a majority, individuals can evade taxation of their labor-time (by destroying it), but cannot avoid taxation of the land they own. One result is that the compromise tax rate on land is higher than that on labor. This contrasts with the classical normative result that in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Agents make utility maximizing labor-leisure choices subject to a budget constraint ' I would like to thank Robert Aumann, Roy Gardner, Mordecai Kurz, Martin Osborne, Hugo Sonnenschein, and Padmanabhan Srinagesh for helpful comments on an earlier draft. Our example is in keeping with the earlier results of Gardner [6] and Osborne [8] who have demonstrated that other well motivated changes in the Aumann and Kurz framework may also result in tax rates of less than 50 per cent. Of course, all errors remain my responsibility.…”
Section: Introduction In a Pioneering Set Of Articles [2 3 4] Aumansupporting
confidence: 90%
“…Agents make utility maximizing labor-leisure choices subject to a budget constraint ' I would like to thank Robert Aumann, Roy Gardner, Mordecai Kurz, Martin Osborne, Hugo Sonnenschein, and Padmanabhan Srinagesh for helpful comments on an earlier draft. Our example is in keeping with the earlier results of Gardner [6] and Osborne [8] who have demonstrated that other well motivated changes in the Aumann and Kurz framework may also result in tax rates of less than 50 per cent. Of course, all errors remain my responsibility.…”
Section: Introduction In a Pioneering Set Of Articles [2 3 4] Aumansupporting
confidence: 90%
“…Carter failed to achieve his objectives; Reagan succeeded. From a formal perspective, Aumann and Kurz (1977) present a cooperative game solution to the tax-transfer problem; see also Gardner (1981) Osborne (1984, and Peck (1986).…”
Section: Public Borrowingmentioning
confidence: 99%
“…*Other interesting variants of the Aumann-Kurz model are presented in Gardner (1981Gardner ( , 1984) and Osborne (1979Osborne ( , 1984. Aumann, Kurz and Neyman (1983) apply the Aumann-Kurz framework to the provision of public goods.…”
Section: Introductionmentioning
confidence: 99%